“Pink round stones”—rhodolith beds: an overlooked habitat in Madeira Archipelago - Neves, Pedro A. (2021)
Despite its worldwide distribution in sedimentary infralittoral and circalittoral bottoms, rhodolith beds have been the subject of fewer studies than other nearshore communities, like kelp forests and coral reefs. This is also the case in Madeira archipelago (Eastern Atlantic), where until recently our knowledge on rhodolith beds was limited to a few references to its occurrence and species composition. In the course of an ongoing habitat-mapping project developed in Madeira, observations revealed that rhodolith beds are more common and extensive than previously supposed. The habitat maps for these beds in Madeira archipelago here presented are the first ever produced for the region. They reveal a total of 46 rhodolith beds at eleven different locations spread across three islands (Madeira, Desertas and Porto Santo), with areas ranging from 776 to 101,081 m(2) and at depths between 12 and 35 m. Author's observations, as well as the results suggest that more rhodolith beds are likely to exist in the archipelago, particularly at greater depths and unexplored locations. The application of molecular systematic tools for the identification of rhodolith-forming species revealed the occurrence of four species belonging to the genera Lithothamnion and Phymatolithon. This latter genus is represented by a single species which is commonly found in rhodolith beds of the archipelago. Genetically, our results show similarities both with the rhodolith communities from the Canary islands and the Algarve (south of Portugal) and highlight the singularities of the archipelago's marine flora. The new array of data here presented is deemed essential for an effective management and conservation of these important and sensitive habitats.